A Correlative Study Between IVIM-DWI Parameters and the Expression Levels of Ang-2 and TKT in Hepatocellular Carcinoma - Zheng, Jing; Gong, Xue Qin; Tao, Yun Yun; Wang, Ran; Yang, Gang; Li, Jing Dong; Ren, Tian; Li, Zu Mao; Yang, Cui; Wang, Wei Cheng; Yang, Lin; Zhang, Xiao Ming (Frontiers in Oncology, 2021)
Objective: To study the correlation between intravoxel incoherent motion diffusion weighted imaging (IVIM-DWI) parameters and angiopoietin-2 (Ang-2) and transketolase (TKT) expression levels in hepatocellular carcinomas (HCCs). Materials and methods: Conventional non-enhanced MRI and IVIM-DWI and dynamic contrast MRI were performed in 61 patients with HCC before surgical treatment. The IVIM-DWI parameters, such as apparent diffusion coefficient (ADC), slow apparent diffusion coefficient (D), fast apparent diffusion coefficient (D*) and fraction of fast apparent diffusion coefficient (f), were calculated with the Function-MADC software. The expression of Ang-2 and TKT of HCC were detected by immunohistochemistry staining and classified into two grades. Independent sample t test was used to compare the parameters differences between the two groups. Spearman rank correlation test was used to analyze the correlation between IVIM-DWI parameters and Ang-2 and TKT expression levels in HCCs. Results: The D* and f values in high Ang-2 group were significantly higher than those in low Ang-2 group; ADC and D were not obviously different in the two groups. The expression of Ang-2 showed positive correlations with the D* and f; but not ADC and D. The ADC and D values in the high TKT group were significantly lower than those in low TKT group; but both the differences of D*and f were not significant in the two groups. TKT expression showed a negative correlation with the ADC and D; but not D* and f. Conclusion: IVIM-DWI can be used to evaluate Ang-2 and TKT expression.